Development of a Secured Vehicle Spot Detection System Using GSM - F. Hussein, Loay; Ben Aissa, Anis; Abdalla Mohamed, Islam; Alruwaili, Saed; Alanzi, Abdalazi (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The number of vehicles stolen is increasing annually. The alarm system for vehicles is commonly used to expose the burglars publicly to make a scene. If the vehicle owner is far away, it will be hard to distinguish the threat to the vehicle from the intruder. To deter such crime, there should be a safer protection mechanism for vehicles around the globe. Moreover, overcrowd parking lot problems have always been an issue. Nevertheless, it became even worse with the progressing urbanization and population expansion. Anyone may have experienced that moment of panic when you realize you have no idea where you parked your vehicle. Note that, the keyless remote control of vehicles has a short-range radio transmitter. It usually can reach up 5–20 meters. Therefore, this paper develops a proposed system that is used for detecting vehicle location using Global System for Mobile Communications (GSM). It is basically capable to switch ON and OFF vehicle alarm system to detect the location of the vehicle in a crowded area. PIC microcontroller that has been embedded in the system programmed using C language. The intelligent proposed system also designs to enhance the security feature for the transportation era. The proposed system offers better service and cost-effective for the vehicle owners.